2016
DOI: 10.4110/in.2016.16.2.126
|View full text |Cite
|
Sign up to set email alerts
|

Effect of IL-4 on the Development and Function of Memory-like CD8 T Cells in the Peripheral Lymphoid Tissues

Abstract: Unlike conventional T cells, innate CD8 T cells develop a memory-like phenotype in the thymus and immediately respond upon antigen stimulation, similar to memory T cells. The development of innate CD8 T cells in the thymus is known to require IL-4, which upregulates Eomesodermin (Eomes). These features are similar to that of virtual memory CD8 T cells and IL-4-induced memory-like CD8 T cells generated in the peripheral tissues. However, the relationship between these cell types has not been clearly documented.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…In support of our conclusion, it has been reported that the administration of IL-4/anti-IL-4 antibody complexes into naïve B6 mice as well as OT-I TCR transgenic mice could induce the generation of memory-like CD8 T cell in the periphery. 36 It is conceivable that IL-15—which is also critical for CD8 T VM cell development and can induce the expansion of CD8 T VM cells in vivo 25,26,37 — could partially compensate the absence of IL-4 or IL-4Rα, particularly when diverse cellular subsets are engaged during complex immune responses to infections (Figure 2d,e). However, it is less clear how this occurs upon the selective activation of iNKT cells by αGalCer (Figure 2c).…”
Section: Discussionmentioning
confidence: 99%
“…In support of our conclusion, it has been reported that the administration of IL-4/anti-IL-4 antibody complexes into naïve B6 mice as well as OT-I TCR transgenic mice could induce the generation of memory-like CD8 T cell in the periphery. 36 It is conceivable that IL-15—which is also critical for CD8 T VM cell development and can induce the expansion of CD8 T VM cells in vivo 25,26,37 — could partially compensate the absence of IL-4 or IL-4Rα, particularly when diverse cellular subsets are engaged during complex immune responses to infections (Figure 2d,e). However, it is less clear how this occurs upon the selective activation of iNKT cells by αGalCer (Figure 2c).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Park et al reported that some T cells with a memory-like phenotype in the thymus respond immediately to antigenic stimulation [ 42 ]. These T cells include NKT cells, PLZF + T-T CD4 (or T-CD4) T cells, H2-M3-specific T cells, mucosal-associated invariant T (MAIT) cells, CD8 αα + intraepithelial T cells, Eomes + natural Th1 cells, and innate CD8 T cells expressing Eomes [ 42 44 ]. Jacomet et al reported strong evidence for the presence of innate-like CD8 T cells in humans and showed that they are Eomes positive [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conversion of a naïve CD8 + T cells to the innate phenotype may also occur in SLO in the presence of IL-4 as reported by others[13, 18, 57, 58]. Moreover, it has been demonstrated that even conventional αβ memory CD8 T cells are able to exert innate-like functions in response to heterologous challenge (e.g.…”
Section: Discussionmentioning
confidence: 60%
“…Over the years, innate CD8 + T cells have been further characterized based on their phenotypic and functional properties[15]. During their thymic maturation, innate CD8 + T cells up-regulate CD44 and CD122 expression and also acquire high cytotoxic and cytokine production capacities, while conventional memory T cells adopt these characteristic in secondary lymphoid organs (SLO)[1618]. Other features of innate CD8 + T cells include 1: they exert their cytotoxic activity in an Ag-independent manner, 2: they highly depend upon IL-15 for proliferation and 3: they are able to rapidly produce interferon-gamma (IFNγ) when stimulated by IL-12 and IL-18 as response similar to that of NK cells[1921].…”
Section: Introductionmentioning
confidence: 99%